Sikap dan Preferensi Konsumen Terhadap Keputusan Pembelian Buah Pisang Ambon dan Cavendish di Kota Pangkalpinang - Alvero, Sri Rani Zhores; Karsiningsih, Eni; Setiawan, Iwan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research aims to analyze consumer attitudes and preferences regarding purchasing decisions for Ambon bananas and Cavendish bananas in Pangkalpinang City. Data collection was carried out from August to September 2023 in Pangkalpinang City. The sampling method used was purposive sampling with a sample size of 100 respondents. Data analysis using Multiattribute Fishbein and Conjoint. The results of the research show that there are differences in consumer attitudes and preferences between Ambon bananas and Cavendish bananas. Consumer attitudes towards the attributes that are most considered in purchasing decisions for Ambon bananas are taste, price, skin cleanliness, size and skin color, respectively, while for Cavendish bananas namely skin cleanliness, skin color, taste, price and size. Consumer preferences for Ambon bananas in Pangkalpinang City are bananas that have a sweet taste, bananas that are > 14 cm long, greenish yellow in color, fairly cheap prices, and bananas that have skin that has no spots. The order of importance values explains the attributes of Ambon bananas that consumers pay most attention to when buying bananas, namely the taste of the banana, the price of the banana, the cleanliness of the banana peel, the size of the banana, and the color of the banana peel. Consumer preferences for Cavendish bananas are bananas that have a sweet taste, bananas that are > 14 cm long, have a yellow skin color, a fairly cheap price, and bananas that have skin that has no spots. The order of importance values explains the attributes of Cavendish bananas that consumers pay most attention to when buying bananas, namely the taste of the banana, the color of the banana peel, the cleanliness of the banana peel, the size of the banana and the price of the banana.